Analisis Natural Weathering pada Komposit Recycled Polypropylene dan Serat Bambu - Arianti Ramadhani; Indah Widiastuti (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
Abstract. The main objective of this study was to analyze the effect of Natural Weathering on the tensile strength and microstructure of recycled polypropylene (rPP) composites with bamboo fiber reinforcement. The rPP-bamboo composite specimens were made using extrusion molding and injection molding machines. The weight fraction used in making the specimens was 10% bamboo fiber and 90% rPP. The rPP-bamboo samples were tested with 3 variations of exposure time, 0 months (without exposure), 1 month and 2 months according to ASTM D1435-05 standard. From the 3 variations of exposure, a tensile test was carried out with the ASTM D638 type V standard to evaluate the value of tensile strength, modulus of elasticity and elongation. Then SEM (Scanning Microscopy Electrone) was performed to see the microstructure of the composite. The results showed that the tensile strength at exposure time of 0 months, 1 month and 2 months was 18.1 MPa with an elongation of 5%, 19.5 MPa with an elongation of 6.4% and 19.3 MPa with an elongation of 6.6%. Young's modulus values showed a decrease with increasing exposure time, ranging from 222 MPa in the sample without exposure to 141 MPa at an exposure time of 2 months. With SEM it is known that, the microstructure of the composite at the beginning of exposure shows a strong bond between the fiber-matrix even though there are some voids in the specimen. At 2 months of exposure, it was seen that there was a gap between the matrix and bamboo due to the hydrophilic nature of bamboo fiber.